MAKING WHIPPED CREAM OR GETTING HIGH: PRODUCT MISUSE OR A FAILURE TO WARN? (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
This paper will consider several legal issues presented by this scenario: Is the Whip-it! a defective product?  Is the manufacturer or the seller of the Whip-it! liable for not properly warning a prospective plaintiff about the dangers inherent in the use of the product? Is Walter a foreseeable user of the product? Has the plaintiff misused the product to such an extent that he or she would be unable to recover for any injuries?  Would any other defenses be potentially available to the defendant?  These questions will be analyzed in the context of Starn v. Smoke Island and Jenkins v. W.L. Roberts, Inc.